The Influence of Shopping Lifestyle and Discounts on Impulsive Buying of Fashion Products (A Study among Generation Z Shopee Users in Pekalongan) - Rizky Andrean; Syifa Rohmah; Nurul Khikmah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The rapid development of Shopee e-commerce in Indonesia not only brought various positive impacts but also negative impacts including impulsive buying behavior. This study aims to examine the influence of shopping lifestyle and discounts on impulsive buying of fashion products at Shopee e-commerce among Generation Z Consumers in Pekalongan. This study is a survey-based field research with a quantitative approach. Data collection in this study was carried out using a Google Form questionnaire as an instrument. The sample in this study is 96 Generation Z in Pekalongan who used Shopee E-Commerce. The data analysis method is multiple linear regression analysis. Based on the results of data analysis, this study found that shopping lifestyle and discounts had a positive and significant effect on impulsive buying of fashion products on Shopee e-commerce among Generation Z in Pekalongan